2014
DOI: 10.1177/2325967114s00070
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopy Skills Development with a Surgical Simulator: A Comparative Study in Orthopaedic Surgery Residents

Abstract: Objectives:Traditional resident assessment of orthopaedic surgical technical proficiency relies exclusively on subjective parameters. More standardized objective measures are needed to ensure training consistency and surgical competency. The purpose of this study was to determine if orthopaedic surgery residents who train with a virtual reality simulator can lead to improved arthroscopy performance and to determine if a standardized arthroscopic shoulder and knee test were appropriate means for evaluating a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 0 publications
1
40
0
2
Order By: Relevance
“… 19 , 24 , 26 , 32 , 37 There is a steep learning curve associated with arthroscopic surgery for orthopaedic surgery trainees. 9 , 33 Extensive hands-on training is typically required to develop surgical competency. 32 , 33 The current minimum number of cases may not be sufficient to develop competency in arthroscopic surgery.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“… 19 , 24 , 26 , 32 , 37 There is a steep learning curve associated with arthroscopic surgery for orthopaedic surgery trainees. 9 , 33 Extensive hands-on training is typically required to develop surgical competency. 32 , 33 The current minimum number of cases may not be sufficient to develop competency in arthroscopic surgery.…”
mentioning
confidence: 99%
“… 9 , 33 Extensive hands-on training is typically required to develop surgical competency. 32 , 33 The current minimum number of cases may not be sufficient to develop competency in arthroscopic surgery. 30 Price et al 32 found that it takes about 170 procedures before a surgeon develops consultant-level motor skills in knee arthroscopic surgery.…”
mentioning
confidence: 99%
See 3 more Smart Citations